PENGARUH WORD OF MOUTH, BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN LIPSTIK PIXY (MOTIVASI, 2023)
Purpose– This study aims to determine the effect of Word Of Mouth, Brand Image and Brand Awareness partially and simultaneously on purchasing decisions of Pixy lipstick in Alang-Alang Lebar DistrictDesign/methodology– An associative type of marriage. The number of samples of Sajrone Panliten Iki Yaiku is 100 respondents. The sampling technique is purposive sampling. Findings - The results of nuduhake analysis show the positive influence of word of mouth, brand image and brand awareness on the decision to buy Pixy lipstick in Alang-Alang Lebar District. The results of Nuduhake Manawa's research on word of mouth, brand image and brand awareness simultaneously have a significant influence on the decision to buy Pixy lipstick in Alang-Alang Lebar District, While partially word of mouth, brand image and brand awareness have a positive and significant effect on the decision to purchase Pixy lipstick in the Alang-Alang Lebar The results of the coefficient of determination nuduhake yen gedhene contributed to word of mouth, brand image and brand awareness marang in purchasing decisions for Pixy lipstick in Aalng-Alang Lebar District, amounting to 60.7%, while the remaining 39.3% was influenced by other variables not included in research. this.